Acoustic gradient surfaces and gradient-index surfaces: Principles and applications on noise control. (1st January 2019) - Wang, Xu; Yu, Wuzhou; Jiang, Zaixiu; Wang, Xiaonan; Mao, Dongxing
Abstract: Gradient surfaces (oblique reflection surfaces) and gradient-index surfaces (surfaces engraved by a series of 1/4 wavelength tubes with linearly growing length) are two solutions on manipulating the reflected sound field. For a high-rise building built close to a traffic road, implementing these two solutions in balcony ceiling design on upper floors both provide remarkable noise insertion losses. This paper presents a systematical comparison between these two surfaces, theoretically and numerically. Our results reveal their distinct underlying working mechanisms: one works by its profile (a macroscopy effect), while the other works by the multiple interferences from its distribute surface impedance (a microscopy effect). The advantage of the gradient-index surface on shielding the balcony region is further demonstrated. This paper may pave the way for the application of the gradient-index surfaces in environmental noise control.